Analysis of Contractual Compliance and Financial Alignment in Productive and Investment Products within Sharia Cooperative - Muhamad Komarudin; M. Rasyid Guntur Pratomo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The financing framework of Benteng Mikro Indonesia (BMI) Sharia Cooperative encompasses various products, notably those categorized as productive and investment financing. Productive financing is implemented through murabahah and musharakah contracts, whereas investment financing utilizes istisna and ijarah agreements. This research seeks to provide a comprehensive examination of the alignment between contractual structures and the financing products offered by BMI Sharia Cooperative. Employing a descriptive qualitative approach, data were collected through interviews and secondary sources, including the cooperative’s official website, reports, and operational guidelines. Findings reveal that murabahah in productive financing and istisna in investment financing conform to DSN-MUI fatwas. Conversely, the ijarah contract demonstrates partial non-compliance, particularly regarding the determination of ujrah (compensation), which is calculated based on the loan amount rather than the benefits derived. Furthermore, while musharakah is generally appropriate, its application to agriculture and livestock-based products is less suitable due to seasonal returns tied to harvest cycles rather than monthly income.